Nutrition concepts for elite distance runners based on macronutrient and energy expenditure - Schröder, S.; Fischer, A.; Vock, Ch.; Böhme, M.; Schmelzer, C.; Döpner, M.; Hülsmann, O.; Döring, F. (Journal of Athletic Training, 2008)
Elite distance runners (EDR) must optimize their nutrition to maintain their demanding training schedules.